Ulnar Buttress Arthroplasty without Ulnar Stump Stabilization for Giant Cell Tumor of Distal Ulna - Kapoor, Love; Kumar, Venkatesan S.; Ansari, Mohammed T.; Khan, Shah A. (Journal of Wrist Surgery, 2023)
Purpose Reconstruction and stabilization of ulnar stump after distal ulna tumor resection is still a matter of debate. We present the outcomes of ulnar buttress arthroplasty without stabilization of the ulna stump in giant cell tumor of bone (GCTB) of the distal ulna.Methods Evaluation of functional outcome was performed using Musculoskeletal Tumor Society 93 (MSTS93) score, Modified Mayo Wrist score (MMWS), and Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire. We also assessed the hand grip strength, range of motion at the wrist, and ulnar carpal translation.Results The study included 8 patients with Campanacci grade 3 GCTB of the distal ulna with a mean follow-up of 35.5 ± 9.1 months. The mean resection length was 7.7 ± 1.3 cm. The mean hand grip strength on the operated side was noted to be 90 ± 0.04% of the contralateral side. Mean MSTS93 score was 27.9 ± 1.25, mean MMWS was 86.9 ± 4.58%, and the mean DASH score was 4.9 ± 1.67, depicting a good to excellent functional outcome with low degree of disability. No radiocarpal instability, ulnar carpal translation, prominence, or instability of the proximal ulnar stump was noted in any patient.Conclusion Reconstruction of the distal radioulnar joint using iliac crest bone graft for ulnar buttress without stabilization of the ulnar stump after resection of the distal ulna is an effective reconstruction option with good functional outcome and preservation of good hand grip strength.Level of Evidence Level IV, Therapeutic study
Keywords: ulna buttress arthroplasty; distal ulna tumors; DRUJ reconstruction